Isaac Newton and the transmutation of alchemy - Fanning, Philip Ashley (North Atlantic Books, 2009)
The christianization of alchemy – John Dee puts alchemy on a new footing – Dee's angelic mission – Francis Bacon's mask – The Rosicrucian furor – Defeat and revival – Alchemy divided – Isaac Newton, alchemist – The advent of modern science
Includes bibliographical references (p. 229-233) and index
Keywords: Biografie; Newton; Isaac; Newton; Isaac 1642-1727; Alchemy; Physics; Science; Physicists